Impatiens agastyamalayensis stat. nov. (Balsaminaceae)—A reassessment of Impatiens rufescens var. agastyamalayensis and rediscovery of the plant from the Western Ghats, India - Joe, Alfred; Bhaskar, V.; Sabu, Mamiyil (Phytotaxa, 2017)
Impatiens rufescens var. agastyamalayensis was described based on a herbarium specimen of C.A. Barber collected in 1901 from Agastyamala. It has now been rediscovered from the same locality after more than a century. Present studies on fresh specimens revealed that the characters are strong enough to elevate the variety to species level, I. agastyamalayensis stat. nov. A detailed description and color photographs are given for easy identification of the species. Detailed notes on seed hair and pollen morphology of I. agastyamalayensis are also provided.